Prognosis and survival of lung cancer in the elderly - Souilah, Souad; Djami, Nassima (International Journal of Medicine, 2024)
Introduction: In our department, from 2012 to 2020, 33.3% of patients treated for lung cancer were over 70 years old. Our study aimed to estimate overall survival and investigate the significance of prognostic factors in a population of 308 patients aged over 70 with lung cancer, collected from January 2012 to June 2020. Methods: The initial assessment included at least a bronchoscopic examination and thoracic computed tomography. Survival rates were calculated using the Kaplan-Meier method and presented with 95% confidence intervals. The Log-Rank test was utilized for the comparison of survival curves. Results: The 308 cases (9.6% females, 90.4% males) included 92.2% NSCLC (49.6% squamous cell, 45.4% adenocarcinomas) and 7.8% SCLC. The median age at diagnosis was 74 years, 14.6% were non-smokers, and 55.8% were former smokers. 67.9% of patients had at least one comorbidity, 1.6% had a PS equal to 0, and 28.2% had a PS ≥ 2. TNM staging found 9.2% of cases at stages I and II; 31.2% at stage III, and 59.7% at stage IV. The median overall survival was 8.312 months [6.947-9.678], and the 1-year survival rate was 35.1%. Better survival was correlated with female gender, absence of smoking, PS ≤ 1, and TNM staging. Conclusion: All standard therapeutic options for bronchial cancer can be considered in the elderly, but physiological aging and the prevalence of comorbidities alter the risk-benefit ratio of treatments. This emphasizes the need for the implementation of a comprehensive management strategy for this segment of society.